Distribution of elastic stress as a function of temperature in a 2-μm redistribution line of Cu measured with X-ray nanodiffraction analysis - Wei-You Hsu; I-Hsin Tseng; Ching-Yu Chiang; K.N. Tu; Chih Chen (Journal of Materials Research and Technology, 2022)
We investigated the lattice strain of nano-twinned Cu (nt-Cu) and regular Cu redistribution lines (RDLs) at 215, 300, 375 and 434 K using x-ray nanodiffraction; this technique has spatial resolution 100 nm. We found that the largest thermal strain or stress appeared at the corner of a Cu line at which the line turns 90°. As the maximum thermal stress in both Cu lines did not exceed the yield strength of Cu, there was no plastic deformation at the highest temperature, 434 K. There was, however, a stress gradient in the corner, which might cause early failure in thermal cyclic tests. In nt-Cu lines, the stress value in the corner is 4.5% greater than the neighbor area at 375 K, and 7.4% greater at 434 K. The maximum stress of nt-Cu is 344.6 MPa at 434 K; the maximum stress of regular Cu is 363.8 MPa.